Oceans, Rivers and Lakes: Energy and Substance Transfers at Interfaces 1998
DOI: 10.1007/978-94-011-5266-2_10
|View full text |Cite
|
Sign up to set email alerts
|

Role of fish communities in particulate organic matter fluxes between salt marshes and coastal marine waters in the Mont Saint-Michel Bay

Abstract: Among the 90 fishspecies censused in the Mont Saint-Michel Bay (France), 23 colonise and forage in the salt marshes during flood. Therefore, this environment may play an important trophic and nursery role for these species. This community is largely dominated by mullets (81% of the biomass), Liza ramada and secondarily L. aurata. But gobies (mainly Pomatoschistus minutus and P. lozanoï) and sea bass (Dicentrarchus labrax) are also present; they represent respectively 11% and 4% of the biomass. During the tide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(69 citation statements)
references
References 27 publications
(7 reference statements)
0
68
1
Order By: Relevance
“…In fact, only a few fish species are able to assimilate salt marsh primary production directly or indirectly; this is the case for mullets Liza and Mugil spp., sand gobies Pomatoschisus spp. and sea bass Dicentrarchus labrax in the MontSaint-Michel Bay (Laffaille et al, 1998(Laffaille et al, , 2002. Salt marsh primary production is essentially assimilated by many invertebrates, and especially by Orchestia gammarella and mysids in European salt marshes (Zagursky and Feller, 1985;Créach et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, only a few fish species are able to assimilate salt marsh primary production directly or indirectly; this is the case for mullets Liza and Mugil spp., sand gobies Pomatoschisus spp. and sea bass Dicentrarchus labrax in the MontSaint-Michel Bay (Laffaille et al, 1998(Laffaille et al, , 2002. Salt marsh primary production is essentially assimilated by many invertebrates, and especially by Orchestia gammarella and mysids in European salt marshes (Zagursky and Feller, 1985;Créach et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The rest of the time the salt marsh, including tidal creeks and vegetated tidal flats, is emerged. Thus, this complex is colonized by fish and marineeestuarine invertebrates such as mysids, amphipods and decapods only for very short periods (1e2 h) during the spring tides when the vegetated creeks and the vegetated intertidal surface are accessible (Laffaille et al, 1998(Laffaille et al, , 2000a. Other macro-invertebrates are semi-terrestrial (e.g.…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Liza carinata commonly inhabit tropical and warm-temperate estuaries (McDowall, 1988;Blaber, 1997;Pombo et al, 2005). Laffaille et al, 1998;Laffaille et al, 2002;Torras et al, 2000;Cardona, 2001;and Almeida, 2003 indicated that mugilidae play a crucial ecological role where this fish community appears to be particulate organic matter transporter and could play a significant role in the global energy budgets of environment. This fish are valuable food sources and ecologically important as primary consumer at coastal and estuarine food chains, and also very representative species for rearing in fish farms (El-Halfawy, 2004;Katsugawa et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Animal movement is an important ecological process that determines the spatial, demographic and genetic structure of populations (McCauley, 1995;Hanski and Gilpin, 1997;Wiens, 2000) and links levels within trophic and nutrient hierarchies through the transport of material (including biomass) (e.g. Deegan, 1993;Kneib, 1997b;Marguillier et al, 1997;Laffaille et al, 1998). Movement paths of individuals and populations reflect both ecological and evolutionary responses to environmental heterogeneity (Southwood, 1977;Levin et al, 1984;Cohen and Levin, 1991).…”
Section: Introductionmentioning
confidence: 99%